Internalization of Teacher Professional Ethics in Collaborative Islamic Religious Education Learning - Nur Faila Suranti; Musrifatun Nisak; Badrus Sodik; Abd. Mukhid; Suci Chanisa; Dwi Yunita Sumiantika (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The integration of professional ethics into classroom practice is essential for enhancing the quality of teaching and fostering meaningful student engagement. This study aims to examine the internalization of teacher professional ethics values through collaborative learning strategies in Islamic Religious Education (IRE) at SMPN 7 Pamekasan. A qualitative approach with a descriptive design was employed to explore how professional ethics are manifested in the teaching and learning process. Data were collected through classroom observations, semi-structured interviews with Islamic Religious Education teachers and students, and documentation analysis. The findings reveal that implementing collaborative learning provides a conducive environment for the internalization of professional ethical values, including responsibility, discipline, honesty, fairness, exemplary behavior, and effective communication. These values are reflected in teachers’ interactions with students, classroom management practices, and the facilitation of group-based learning activities. Furthermore, collaborative learning encourages active participation, mutual respect, teamwork, and shared responsibility among students, thereby improving both academic and social learning outcomes. The study concludes that the successful internalization of teacher professional ethics significantly contributes to the effectiveness of collaborative learning in Islamic Religious Education. Therefore, strengthening teachers’ ethical competencies is crucial for creating an engaging, inclusive, and value-oriented learning environment.